MENANGKAL BERITA HOAX MENURUT AL-QURAN SURAH AN-NUR AYAT 11 - Hermanto, Edi (Jurnal Ushuluddin, 2025)
Islam as a religion of rahmatan lil 'alamin brings teachings that remain relevant throughout the ages, including in today's digital era. The Qur'an is the main guide in solving various life problems in a correct and wise way. This research aims to analyze the importance of ethics in receiving, verifying, and disseminating information based on the values contained in Q.S. An-Nur verses 11-20. It also aims to provide an understanding of how the principle of tabayyun can be applied in the digital era to prevent the spread of hoaxes and slander. The method used in this research is library research, by studying the Qur'an, books, journals, articles, and other sources that discuss ethics in information. The results show that tabayyun, which is the attitude of caution and clarification of the news received, is very important to prevent slander and the spread of hoaxes. In this digital era, information is easily spread through social media such as WhatsApp, Instagram, Facebook, and TikTok. However, this convenience also brings challenges in the form of widespread fake news that can cause damage in society. Q.S. An-Nur verses 11-20 teaches that spreading news without clear evidence is a dangerous act and will bring bad consequences, both in this world and in the hereafter. Therefore, applying the principle of tabayyun in the digital era is a concrete form of practicing Islamic values, maintaining social harmony, and building a society that is more honest and responsible for the information circulating.